Impact of the Elementary School Heads Leadership Behavior on the Teacher’s Morale in School Districts of Pilar - Arong, Lovelyn (JPAIR Institutional Research, 2024)
The study focused on elementary school heads' leadership behaviors and their impact on teacher morale in Pilar's school districts, aiming to provide valuable insights into educational leadership dynamics. It outlines the objectives of analyzing leadership behavior, assessing teacher morale, determining impacts, identifying challenges, describing measures, and proposing a leadership model to address these issues comprehensively. The mixed-methods study used surveys and document analysis to examine how leadership behavior influenced teacher morale. Quantitative methods measured the impact on commitment and assessed various attitudes and challenges. Qualitative methods analyzed leadership behaviors reflected in OPCRF and described measures to address challenges. Findings indicate proactive leadership practices, contributing to positive teacher morale, yet challenges such as workload and communication gaps persist, indicating areas for improvement. Measures to address these challenges include embracing technology, fostering collaboration, and enhancing communication channels to create a supportive and conducive work environment. The proposed Adaptive Transformational School Leadership Behavior and Change Model integrates adaptive and transformational leadership theories, offering a holistic framework to address challenges and drive positive change within educational contexts. In conclusion, the study underscores the crucial role of school leadership in shaping teacher morale and organizational dynamics, highlighting the importance of supportive environments, effective communication, and targeted interventions to enhance educational outcomes and foster a conducive learning environment within Pilar's elementary schools.
Keywords: teacher morale; leadership behaviors; OPCRF; adaptive transformational leadership; educational outcomes; school climate; mixed-methods; policy development; Philippines